2016
DOI: 10.1097/bcr.0b013e31825aeac1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Application of Allogeneic Fibroblast and Autologous Mesh Grafting With the Conventional Method in the Treatment of Third-Degree Burns

Abstract: Wound healing is a multipart process involving different cell types and growth factors. Third-degree burns are usually treated by early excision and skin grafting. Tissue engineering has been developed in this field in response to limitations associated with autografts. Allogeneic fibroblasts on meshed split thickness skin grafts (STSGs) are known to have useful properties in wound healing and can be used to construct a new model of living skin substitute. Fourteen patients were chosen from June 2009 until Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Previous studies have described contraction in mice as a common physiological phenomenon after skin grafting. Park et al (2014) compared the use of splinted versus non-splinted models and demonstrated that the wound generated in the skin of the animal tends to fully shrink and contract after 11 d in non-splinted models, whereas splinted models reduce the contraction rate to near 60 % after 11 d (Gebremeskel et al, 2018;Park et al, 2014). In the present study, the wound contraction percentage reached 61.7 % after 30 d, suggesting a reduction of the wound contraction that may improve re-epithelisation with the grafted tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described contraction in mice as a common physiological phenomenon after skin grafting. Park et al (2014) compared the use of splinted versus non-splinted models and demonstrated that the wound generated in the skin of the animal tends to fully shrink and contract after 11 d in non-splinted models, whereas splinted models reduce the contraction rate to near 60 % after 11 d (Gebremeskel et al, 2018;Park et al, 2014). In the present study, the wound contraction percentage reached 61.7 % after 30 d, suggesting a reduction of the wound contraction that may improve re-epithelisation with the grafted tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous models of human skin, generated by tissue engineering, have been developed to date (Beaudoin Cloutier et al, 2017;Bhowmick et al, 2017;Forouzandeh et al, 2010;Hartmann-Fritsch et al, 2016;Klar et al, 2018;Larouche et al, 2016;Lloyd et al, 2015;Pensalfini et al, 2017;Reuter et al, 2017;Strong et al, 2017;Vig et al, 2017). However, few clinical trials have been conducted to test the biological security (phase I and II assays) of human skin models (Boa et al, 2013;Boyce et al, 2006;Boyce et al, 1999;Boyce et al, 2017;Germain et al, 2018;Moravvej et al, 2016;Yamada et al, 2012). Most of the clinically efficient skin models are organotypic structures, consisting of a dermal substitute of dermal fibroblasts immersed in biocompatible scaffolds and an epidermal layer of keratinocytes seeded on top of the stroma.…”
Section: Introductionmentioning
confidence: 99%
“…The use of amniotic membranes in wound healing is supported by its anti‐inflammatory, antiangiogenic and antifibrotic properties, which can induce keratinocyte proliferation, differentiation and re‐epithelialization through a variety of growth factors . Based on our previous studies, we used FAMS as a cover over the wounds. This resulted in complete closure of some wounds, which was evident by the presence of col VII on IFM after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Skin substitutes are defined as a heterogeneous group of substances that aim to restore the skin barrier function, facilitate wound healing, prevent infections and manage pain. Most skin substitutes are acellular; however, in the last few years increasing attention has been paid to the development of cellular substitutes mainly manufactured using two types of cells: fibroblasts and keratinocytes . Moreover, recent researches also include new cell types such as melanocytes, mesenchymal stem cells (MSCs), epidermal stem cells, hair follicle stem cells and even cell‐based products such as platelet‐rich‐plasma (PRP) …”
Section: Introductionmentioning
confidence: 99%
“…Most skin substitutes are acellular; however, in the last few years increasing attention has been paid to the development of cellular substitutes mainly manufactured using two types of cells: fibroblasts and keratinocytes. [4][5][6] Moreover, recent researches also include new cell types such as melanocytes, 7 mesenchymal stem cells (MSCs), 8 epidermal stem cells, 9 hair follicle stem cells 10 and even cell-based products such as platelet-rich-plasma (PRP). [11][12][13] New approaches for skin TE are focused on combining novel natural or synthetic materials and living cells in several biomedical and pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%